KEKONVERGENAN SKEMA ITERASI DUA PEMETAAN NONEKSPANSIF KE SUATU TITIK TETAP BERSAMA - , BERNADUS SETYA AJI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this final project, we discuss about convergence of an iteration scheme with two nonexpansive mappings to a common fixed point. First, we discuss about the sufficient conditions of a sequence which satisfy an iteration scheme with two nonexpansive self mappings convergence or weakly convergence to a common fixed point. Furthermore, based on the iteration scheme with two nonexpansive self mappings, we solve an iteration scheme with two nonexpansive nonself mappings by inserting a nonexpansive retraction mapping on the previous iteration scheme. In the last section, we investigate the convergence and weak convergence of sequence which satisfy the iteration scheme with two nonexpansive nonself mappings to a common fixed point by using the sufficient conditions of previous iteration scheme.